Penyusunan Modul Fisika Berbasis SETS (Science, Environment, Technology, and Society) Pada Materi Fluida Dinamis Untuk Siswa Kelas XI SMA - Rahmat Taufiq; Sarwanto Sarwanto; Sukarmin Sukarmin (Universitas Sebelas Maret, 2022)
This study aims to: (1) develop a physics module with SETS (Science, Environment, Technology, and Society)-based characteristics and fulfill the scientific literacy aspects of Dynamic Fluid Materials for Class XI High School Students that were developed; and (2) determine the validity of the SETS-based physics module (Science, Environment, Technology, and Society) on Dynamic Fluid Materials for Class XI High School Students which was developed. The research method used is R&D (Research and Development) with the module formulation model adopting the ADDIE developed by Dick & Carry. This procedure was modified to the third stage with the following steps: analysis, design, and development. The research data sources were obtained from two expert validators, two reviewers, and 71 students. Qualitative data were taken through interviews and open questionnaires. Quantitative data were taken through a closed questionnaire and analyzed by descriptive analysis. The conclusions of this research are: (1) the characteristics of the physics module that is compiled using the learning flow with the SETS approach (Science, Environment, Technology, and Society) and contains aspects of scientific literacy; and (2) the feasibility of the physics module from the assessment of expert validators, reviewers' assessments, one-on-one trials, small group trials, and field trials shows that the physics module that is compiled is categorized as suitable for use in physics learning on dynamic fluid materials.